The Factors Affecting the Sociolinguistic and Strategic Competencies in English among Teachers in Higher Education Teachers in Lipa City - Tipan, Allan D. (JPAIR Multidisciplinary Research, 2013)
The study attempted to describe the factors affecting the sociolinguistic andstrategic competencies in English among teachers in Higher Education Institutionsin Lipa City and determine the relationship between the demographic characteristicsand their assessments. The study was done during the school year 2010-2011. ThreeHigher Education Institutions in Lipa City were selected as the research locale. Totalenumeration was used as sampling for the study. Both quantitative and qualitativeresearch methods were employed. The respondents agreed that the factors of contextof acquisition, accommodating speech norms and code switching, degree of contactwith second language users and level of confidence affect their sociolinguisticcompetence. Likewise, they also agreed that the factors of questioning skills and useof non-verbal communication affect their strategic competencies. Variations in termsof the relationships of different demographic characteristics and their sociolinguisticand strategic competencies were also established. A general sense, the teachers' diverse characteristics generated different points of view on how the factors affecttheir competencies. This led to the conclusion that they are the ones responsible why the factors influence their competencies. They should be the ones responsible for affecting culture and not culture to affect their language competencies. It is of greatimportance that teachers should take the initiative to study and systematically use thecompetencies which they can work on. HEI administrators should offer professionaldevelopment seminars as these are necessary for the effective use of the teachers' competencies.
Keywords: competency; sociolinguistic competence; strategic competency; context of acquisition; code switching; confidence questioning skills; non-verbalcommunication